Dualism of Land Management Authority between BP Batam and the Batam Municipal Government: Its Impact on Building Use Right Certificates - Bottor Erikson Pardede; Pristika Handayani (Universitas Internasional Batam, 2025)
The dualism of land management authority between the Batam Indonesia Free Zone Authority (BP Batam) and the Batam Municipal Government has generated persistent legal and administrative challenges in the issuance of Building Use Right Certificates in Batam City. Overlapping authority has resulted in prolonged certification procedures, regulatory inconsistencies, and heightened legal uncertainty, which negatively affect investment realization and the effectiveness of land governance. Despite the existence of comprehensive statutory frameworks, the implementation of HGB certification in Batam continues to encounter structural obstacles arising from fragmented institutional authority. This study aims to examine the impact of the dualism of authority between BP Batam and the Batam Municipal Government on HGB certification services and to propose policy recommendations to enhance legal certainty and administrative efficiency. The research employs empirical legal research using a statutory and phenomenological approach. The findings indicate that the dual authority structure has significantly delayed HGB certification, with more than 1,100 applications pending in 2023 and affected investment values amounting to approximately IDR 2.3 trillion. Divergent documentary requirements, zoning maps, and procedural standards between BP Batam and the municipal government have created duplicative processes and extended verification stages, resulting in certification timelines of up to 180 days for land parcels requiring approval from both authorities. Although BP Batam regulations provide detailed technical guidance and strong formal legal legitimacy, their implementation is frequently misaligned with municipal policies, thereby weakening substantive legal certainty. The study further reveals that limited inter-agency coordination, insufficient integration of information systems, and the absence of binding dispute-resolution mechanisms contribute to recurring land disputes and litigation. The study concludes that resolving land governance dualism in Batam requires regulatory harmonization, clearer delineation of authority, and the establishment of an integrated One Door Service Unit supported by a Batam-specific Online Single Submission system to accelerate certification processes and strengthen legal certainty.